PENGARUH JENIS PERANGKAP DAN FEROMON SEKS TERHADAP TANGKAPAN NGENGAT JANTAN Spodoptera exigua - Agus Dana Permana dan Rostaman . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2006)
Effect of trap design and sex pheromone on the capture of male Spodoptera exigua. This research was to know the effectiveness of two traps and three kinds of pheromone in attracting and catching the male insects of Spodoptera exigua Hubner in shallot field. Two traps were wing trap and bottle trap, whereas pheromones were standard [Z9E12-14Ac + Z9-14OH (10:1)), Ugratas® and virgin females. Traps that were loaded with a kind of pheromone, were placed randomly in shallot field, about 7 meters apart. The numbers of male insects that attracted and caught were recorded in three days for 12 days. The result showed that more male insects were caught in bottle traps than wing traps, and more males attracted in Ugratasïƒ’ than other pheromones.